The role of Pharmacist in optimizing antibiotic therapy. Impact of pharmaceutical consultations on antibiotic and antimicrobial drugs consumption - Daniel Orzechowski; Adrian Bryła; Krystyna Chmal-Jagiełło (Polish Pharmaceutical Society, 2023)
Introduction According to the data provided by the National Antibiotic Protection Program, approximately 50% of antibiotic prescriptions are inappropriate and every tenth hospitalized patient receives antibiotics for unjustified reasons. Overuse of this group of drugs has led to antibiotic resistance, which- according to the European Center for Disease Prevention and Control (ECDC) is a significant clinical problem in Poland. Extended hospitalization time due to infection and costs associated with antibiotic therapy are becoming an important financial problem. The report of the Supreme Audit Office (NIK) estimated them in 2019 at 800 million PLN during one year. Aim The aim of the study was to assess the impact of the introduced pharmaceutical consultations and other elements of antibiotic stewardship on the use of antimicrobial drugs in the Ludwik Rydygier Memorial Specialized Hospital in Krakow. Methods Prescribed second - and thitrd - line drugs vere verified by a pharmacist from The Antibiotics Team during dispensing drugs from The Hospital Pharmacy. After verifying the of antibiotic therapy, the pharmacist approved the dispense of the drug or performed consultations. Results The effect of the efforts carried out by the antibiotic stewardship team is a 35% decrease in the frequency of 2nd and 3rd line anti-microbial drugs dispensed within 2 years. The decrease in the use of carbapenems was 51% and the use of intravenous fluoroquinolones was reduced by 79%. Conclusions The prospective pharmacist control at The Ludwik Rydygier Memorial Specialized Hospital in Krakow, antibiotic therapy was associated with changes in the structure and quantity of antimicrobial drugs dispensed. It is not clear what type of pharmacist activity (empiric ntibiotics therapy consultations, de-escalation, drug concentration-monitored therapy consultations) contributed the most to reducing the number of drugs dispensed. This issue requires further research and is particularly important in connection with the implementation of clinical pharmacy services in Poland, their evaluation and standardization.